Bioinspired Polymers: Sequence Programmable Peptoid Polymers for Diverse Materials Applications (Adv. Mater. 38/2015). (8th October 2015) - Knight, Abigail S.; Zhou, Effie Y.; Zuckermann, Ronald N.
<x xml:space="preserve">Abstract</x> Peptoid polymers combine the sequence programmability of biopolymer systems with the robustness and chemical diversity of traditional synthetic polymers. On page 5665, R. N Zuckermann and co‐workers review recent developments in this emerging field, many of which have been pioneered at the Molecular Foundry, with an emphasis on combinatorial synthesis, structural control, and materials applications.